Architecture and the Public Sector: Image as Narrative in Brazilian Architecture - Cotrim, Marcio (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2018)
This article uses two photographs to reveal a set of fundamental arguments about Brazilian architecture that were forged in the late 1930s and consolidated in the 1940s and 1950s. These arguments can be summarized as the Corbusian matrix (the vertical prism), the pretense of the adaption of buildings to the local climate (the use of the cobogó and the glass curtain), the coexistence of the past and present (a photographic overlap of buildings from different periods) and – what interests us most in this article – the association with the state (which either sponsored or utilized the buildings in question). The second section of the article gives an overview of the relationship between architecture and the public sector with the support of other photographs.